THE ROLE OF DIGITAL STORYTELLING IN IMPROVING THE COMPETITIVENESS OF CREATIVE ECONOMY MSMES - Djou, Sitti Husna Noviana; Nasila, Rahmat; Husain, Putra Arisandi; Lukum, Marlon Mohamad (LP2M Universitas Bina Mandiri Gorontalo, 2025)
This research examines the crucial role of digital storytelling in improving the competitiveness of Micro, Small and Medium Enterprises (MSMEs) in the creative economy sector. In an increasingly competitive and digitized business landscape, MSMEs are faced with the challenge of attracting consumer attention and building brand loyalty. Digital storytelling, as a marketing communication strategy that utilizes narratives through various digital platforms, offers an innovative solution to create emotional connections with audiences. This research method uses qualitative approach with a comprehensive literature study of relevant accredited national journals. The analysis shows that digital storytelling enables MSMEs to communicate the unique value of their products or services, build a strong brand identity, and differentiate themselves from competitors. Effective implementation of digital storytelling is proven to increase brand visibility, expand market reach, and ultimately, contribute to improving the competitiveness of creative economy MSMEs in domestic and global markets. The practical implication of this research is the recommendation for MSMEs to integrate digital storytelling as a core component in their marketing strategy, supported by adequate training and mentoring.